Contributions to the knowledge of the Quediina (Coleoptera, Staphylinidae, Staphylinini) of China. Part 32. Genus Quedius Stephens, 1829. Subgenus Distichalius Casey, 1915. Section 3 - Smetana, Aleš (Zootaxa, 2009)
The purpose of this paper is the need to correct mistakes appearing in a paper by Zheng, Wang and Liu (Zheng et al. 2008), and to offer a few considerations concerning the peer reviewing of scientific papers.